Clump-scale chemistry in the NGC 2264-D cluster-forming region. (13th October 2021) - Taniguchi, Kotomi; Plunkett, Adele; Shimoikura, Tomomi; Dobashi, Kazuhito; Saito, Masao; Nakamura, Fumitaka; Herbst, Eric
Abstract: We have conducted mapping observations toward the n3 and n5 positions in the NGC 2264-D cluster-forming region with the Atacama Compact Array (ACA) of the Atacama Large Millimeter/submillimeter Array (ALMA) in Band 3. Observations with a 10000 au scale beam reveal the chemical composition at the clump scale. The spatial distributions of the observed low upper-state-energy lines of CH3 OH are similar to those of CS and SO, and the HC3 N emission seems to be predominantly associated with clumps containing young stellar objects. The turbulent gas induced by the star formation activities produces large-scale shock regions in NGC 2264-D, which are traced by the CH3 OH, CS, and SO emissions. We derive the HC3 N, CH3 CN, and CH3 CHO abundances with respect to CH3 OH. Compared to the n5 field, the n3 field is farther (in projected apparent distance) from the neighboring NGC 2264-C, yet the chemical composition in the n3 field tends to be similar to that of the protostellar candidate CMM3 in NGC 2264-C. The HC3 N$/$ CH3 OH ratios in the n3 field are higher than those in the n5 field. We find an anti-correlation between the HC3 N$/$ CH3 OH ratio and their excitation temperatures. The low HC3 N$/$ CH3 OH abundance ratio at the n5 field implies that the n5 field is an environment with more active star formation compared with the n3 field.